Atherosclerosis and coronary artery bifurcation lesions: Anatomy and flow characteristics - Stanković Goran; Vukčević Vladan; Živković Miroslav; Mehmedbegović Zlatko; Živković Milorad; Kanjuh Vladimir (Vojnosanitetski Pregled)
nema